Increasing Kang’s Kitchen’s Brand Awareness to Its Target Market through a Promotional Video - Ivan Hendranata (Institute of Research and Community Outreach - Petra Christian University, 2022)
Kang’s Kitchen is a homemade cake and homemade food company that is located in Jakarta. It was established in 2019 at Surabaya when Kang’s Kitchen was still selling homemade Ote-Ote and now the shop is focusing on baking many kinds of cakes. Kang’s Kitchen target market is Instagram users that like to order food or cake from the application. The shop is currently new in Jakarta, so few people know about Kang’s Kitchen and its products. In addition, some competitors sell almost the same products. These make the sales volumes still very low. From the customers’ survey, I found out that the shop lacks brand awareness among its target market. The target market is still unaware of Kang’s Kitchen Unique Selling Points, premium quality and hygienic processing. The solution is, therefore, highlighting the USPs in a video, and upload it in Instagram. By projecting the company’s strengths in Instagram, Kang’s Kitchen followers are expected to increase, and those followers are expected to be loyal customers.